Factors Associated With Hypertension Among Adult Clients in Provincial Hospital - Bhandari, Sarada; Acharya, Devaka Kumari (Journal of Institute of Medicine Nepal, 2025)
Introduction Hypertension is one of the major public health problem and its prevalence is increasing across the countries globally. Most of the factors associated with high blood pressure are modifiable. If they are not addressed timely it would burden to health care system. This study aimed to determine the factors associated with hypertension among the adult clients in provincial hospital. Methods This study is a hospital-based case-control design conducted in Lumbini Provincial Hospital with a total 160 (80 cases and 80 controls) samples. The data was collected by face-to-face interview technique using World Health Organization STEP wise approach to Non-Communicable Disease Risk Surveillance instrument version 3.2 from 18 September 2023 to 13 October 2023. Data were entered in SPSS version-21 and analyzed. Chi-square, crude odds ratio and adjusted odds ratio was calculated. Results Clients having a family history of hypertension are 2.3 times more likely to get hypertension (COR= 2.38, 95% CI= 1.262-4.516, p=0.007). Second hand smoker had 2.4 times more chance of getting hypertension (COR= 2.362, 95% CI=1.262-4.516, p=0.007). Alcohol consumers were likely to have high blood pressure 3.0 times more. Other risk factors were inadequate consumption of fruits and vegetables, physically inactive, having a higher BMI, and having comorbidity. Conclusion Most of the risk factors associated with hypertension are behavioural and could be modified. So, policymakers and healthcare professionals need to conduct awareness programs focusing on lifestyle modifications for the prevention of hypertension and to reduce disability and death.